Designing attributes of a multifunction table using the kansei engineering method - Moh. Zainudin; Ribangun Bamban Jakaria (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2025)
CV JAYA MAKMUR is a company that produces rattan processing and produces furniture made from rattan and wood. This CV can produce 60 pieces of furniture per month and the delivery is 10 tables. The tables produced are ordinary tables generally available on the market. This research aims to obtain a design and prototype of a multifunctional table that is comfortable and practical for consumers using the Kansei Engineering method. The contribution of this research is to help declare Kansei Engineering as a method of processing values ​​as input into product attributes as output. Kansei Engineering's development is a consumer-oriented ergonomics technology that is used to translate consumer feelings as a basis for developing new products. This provides an alternative, namely creating a product design that produces a multifunctional table product that allows achieving this function at a minimum total cost without reducing the quality of the product. Kansei Engineering is needed to produce products that meet consumer needs